ATTITUDE OF ELEMENTARY SCHOOL TEACHERS TOWARDS INCLUSIVE CLASSROOM AT ELEMENTARY STAGE - Mishra, Sabita (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2024)
This study attempted to find out the attitude of elementary school teachers towards inclusive classroom. Teachers’ attitude played a significant role in implementing the inclusive education in classroom. The population of the study comprised of all the elementary teachers of Puri district. 70 teachers were selected through incidental sampling from 20 schools of Nimapara Block of Puri district. Teachers’ attitude towards inclusive classroom was studied based on three demographic variables viz.locality, qualification and experience. The study was descriptive in nature and two tools (attitude scale and questionnaire) were used for data collection. The findings of the study revealed that (i) there was no significant difference in the attitude of rural andurbanteachers towards inclusive classroom (ii) no significant difference was found in the attitude of more qualified and less qualified teachers towards inclusive classroom and (iii) no significant difference was found in the attitude of more experienced and less experienced teachers towards inclusive classroom. However, 90 percent of teachers perceived inclusion as a desirable educational practice because inclusive classroom facilitated participation, encouraged cooperation and enhanced learning achievement of students. Only 10 percent of teachers perceived inclusionnegatively. The study also analysed some of the barriers to the development of successful inclusive practices and suggested the ways to overcome these difficulties and to reconsider the roles, responsibilities and identities of teachers.